A Model-Based Approach to Generate Reactive and Customizable User Interfaces for theWeb Of Things - Bezerra, Jagni D. H.; Souza, Cidcley T. de (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2019: Proceedings of the 25th Brazilian Symposium on Multimedia and the Web, 2019)
The Internet of Things(IoT) is an extension of the Internet on physical devices and everyday objects that has been facing an increase of its heterogeneity (e.g. devices, protocols, services). TheWorld Wide Web Consortium(W3C) has been developing the Web of Things standards(WoT) to address this issue and it is proving to be a feasible solution by using web protocols and the Thing Description(TD) formal model to expose Web Things(WT) properties, actions and events. However, users still deal with heterogeneity when trying to interact withWTs as they need to download specific apps or access different websites to interact with each of them. This paper’s goal is to propose the use of Models at Runtime to enable the creation of a reactive and customizable User Interface(UI) to interact with any WT according to their TD. Reactive in the sense of reflecting changes that occur to the associatedWT in real-time or even changing itself to represent a different WT. Customizable meaning it is designed in a way that the aesthetic aspects are detached from the implementation, allowing developers and designers to personalize them.